Resilience Of Women Survivors Of Sexual Violence Facing Social Stigma In Jambi - Hasnah Delilah; Harmona Daulay; Hadriana Marhaeni Munthe; Badaruddin Badaruddin; T. Ilham Saladin (Jurnal Ilmu Sosial Mamangan, 2024)
This research examines the resilience of women survivors of sexual violence who experience social stigma in Jambi City. The qualitative research method is employed with the aim of providing a comprehensive overview of the resilience of female survivors of sexual violence facing social stigma in Jambi City. In reality, instances of sexual violence in this city persist, leading female survivors to endure social stigma and societal judgment. This social stigma contributes to the victims' feelings of sadness and trauma. The social stigma experienced by these survivors includes stereotypes, labeling, and discrimination. Consequently, negative perceptions from society prompt female survivors of violence to undertake resilient efforts to overcome the sadness and trauma resulting from sexual violence and the associated stigma.